A Theoretical Study On Antimycobacterial Activities Of Nbenzylsalicylamides And N-Benzylsalicylthioamides Derivatives Against Mycobacterium Avium - SUPRATIM RAY, (International Journal of Pharma and Bio Sciences, 2012)
A QSAR study has been attempted on the in vitro antimycobacterial activities of N-Benzylsalicylamides and N-Benzylsalicylthioamides derivatives reported by Dolezal et al. against Mycobacterium avium CNCTC My (330/88) using electrotopological state atom (E-state) parameter. The reported minimum inhibitory concentrations [MIC] of the compounds were determined after 21 days of incubation. Different statistical tools used in this communication are stepwise regression analysis and partial least squares analysis (PLS). All the developed models indicate the importance of connecting moiety methylcarboxamido / methylthiocarboxamido group between two substituted phenyl groups. From the PLS models it has been observed that hydroxyl group has negatively contributed towards activity. The models also indicate the Positive contribution of amino group towards activity. Based on internal validation (Q2), external validation (R2pred) PLS analysis was found to be the best model (Q2=0.624, R2pred=0.756).